Catalysis mechanism of Pd-promoted γ-alumina in the thermal decomposition of methane to hydrogen: A density functional theory study - Salam, M.A. (Elsevier Ltd, 2017)
Thermo-catalytic methane decomposition to elemental hydrogen mechanism in transitional metals (Pd, Ni & Mo) promoted Al2O3 (001) catalyst have been studied using the density functional theory (DFT). Decomposition reactions are spontaneous and favourable above 775 K for all promoter. Pd-promoted Al2O3 (001) catalyst demonstrates a breakthrough decomposition activity in hydrogen production as compared to Nisbnd and Mo-promoted Al2O3 (001) catalysts. The activation energy (Ea) range of the catalysis for Pd promoted Al2O3 (001) catalysts is 0.003–0.34 eV. Whereas, Ni and Mo promoted Al2O3 (001) catalysts display activation energy Ea in the range of 0.63–1.15 eV and 0.04–5.98 eV, respectively. Pd-promoted catalyst also shows a higher adsorption energy (−0.68 eV) and reactivity than that of Ni and Mo promoted Al2O3 (001) catalysts. The rates of successive decomposition of methane are found to be 16.15 × 1012, 15.95 × 1012 and 16.09 × 1012 s−1 for the promoter of Pd, Ni and Mo, respectively. Pd promoted Al2O3 (001) catalyst reduces the methane decomposition temperature (775 K) and deactivation rate significantly. The catalytic conditions and catalyst is promising in producing hydrogen to support hydrogen economy. © 2016 Elsevier B.V.